2023
DOI: 10.1021/acscatal.3c00265
|View full text |Cite
|
Sign up to set email alerts
|

Two Birds, One Stone: Coupling Hydrogen Production with Herbicide Degradation over Metal–Organic Framework-Derived Titanium Dioxide

Abstract: Consumption of contaminated water can have detrimental effects on the health of every living organism on earth. There is, thus, a need to develop novel materials and technologies to purify water. Water is also a source of hydrogen, a clean renewable fuel that can be generated through the action of a photoactive catalyst and the earth's abundant solar energy. Using photocatalysis, we can purify water by removing organic pollutants through the photodegradation reaction (oxidation) and produce hydrogen (H 2 ) thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…Consequently, addressing the generation of AMPA during glyphosate degradation has become a critical concern in mitigating the environmental consequences associated with glyphosate. 165 In their study, Musa et al 166 opted to use glyphosate ( N -phosphonomethylglycine or PMG) as the herbicide of choice for their photocatalytic tests. The investigators proceeded to analyze the relative proportions of PMG and the decomposition products, namely glycine, formic acid, and AMPA, generated in the solution.…”
Section: An Integrated Approach Of Converting Micropollutant Into Fea...mentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, addressing the generation of AMPA during glyphosate degradation has become a critical concern in mitigating the environmental consequences associated with glyphosate. 165 In their study, Musa et al 166 opted to use glyphosate ( N -phosphonomethylglycine or PMG) as the herbicide of choice for their photocatalytic tests. The investigators proceeded to analyze the relative proportions of PMG and the decomposition products, namely glycine, formic acid, and AMPA, generated in the solution.…”
Section: An Integrated Approach Of Converting Micropollutant Into Fea...mentioning
confidence: 99%
“…While the performance of both pristine and doped mixed phases (consisting of both rutile and anatase) was enhanced, the resultant mixed products included formic acid, glycine, and AMPA, with PMG persisting in the system. 166 AMPA, an intermediate of PMG, is known for its adverse environmental impact, primarily involving damage to the carbon–nitrogen bond in PMG. The N, S-doped anatase (NSTA) phase demonstrated both efficient degradation of PMG and the generation of environmentally safe by-products, namely glycine and formic acid.…”
Section: An Integrated Approach Of Converting Micropollutant Into Fea...mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies on photocatalytic degradation of GP employ the metal oxide semiconductor TiO 2 , with a few studies focused on MnO 2 30 . Recently, our group demonstrated complete GP degradation in 5 mM (845 ppm) GP solution after 8 h of irradiation using a nitrogen and sulfur-doped TiO 2 anatase (NSTA) derived from the metal-organic framework (MOF) MIL-125-NH 2 54 . While kinetic investigations revealed that AMPA was formed initially, AMPA was almost entirely degraded after the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, efforts have been made to harness solar energy more efficiently with efficient photocatalysts such as Cu 2 O/TiO 2 , Fe 2 O 3 /TiO 2 , CdS/TiO 2 , and WO 3 /TiO 2 . However, TiO 2 has a wide band gap and absorbs only ultraviolet (4% of the entire solar spectrum), which largely limits its utilization of sunlight, and many solutions have been proposed to solve this problem. For example, it is possible to extend its optical absorption to visible light by doping with various ions, but this usually results in a lower photogenerated charge lifetime. Since photocatalysts modified by vacancies can reduce the complexation rate of photogenerated carriers and enhance photocatalytic performance, the introduction of oxygen vacancies in TiO 2 is expected to be one of the effective strategies to optimize the photocatalytic activity of TiO 2 . , In addition, combinations with other semiconductor materials have emerged. Zhang et al dispersed CdS particles on the surface of MIL-125­(Ti), resulting in a conversion of BA to BAD of about 20.1% .…”
Section: Introductionmentioning
confidence: 99%